2022
DOI: 10.3389/fpsyg.2022.942284
|View full text |Cite
|
Sign up to set email alerts
|

Teacher violence from the perspectives of teachers and students and related factors: A survey in Southern Iran

Abstract: IntroductionTeacher violence is defined as the intentional use of power by teachers against students in a variety of ways, including physical, verbal, psychological, and sexual assault. Victims of school violence are more anxious and insecure than other students. An in-depth and comprehensive study on the prevention of violence in schools is urgent and necessary. We conducted this study to determine teacher violence from the perspectives of schoolteachers and students and related factors.MethodsWe conducted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…sexual coercion in exchange for food, grades or school fees among Zambian girls (Ardestani et al, 2022). The same can be said about South Africa, where female learners are at a significantly higher risk than boys of being sexually assaulted by male teachers at school, according to Nako and Muthukrishna (2018).…”
Section: Restorative Justicementioning
confidence: 96%
See 1 more Smart Citation
“…sexual coercion in exchange for food, grades or school fees among Zambian girls (Ardestani et al, 2022). The same can be said about South Africa, where female learners are at a significantly higher risk than boys of being sexually assaulted by male teachers at school, according to Nako and Muthukrishna (2018).…”
Section: Restorative Justicementioning
confidence: 96%
“…In addition, it was shown that teachers in high schools experienced more violent harassment than those in primary schools (Ozdemir, 2012). On the other hand, teachers frequently use physical and emotional violence against children (Ardestani et al, 2022). At times, school violence is more subtle and is associated with teachers' disengagement, turnover or emotional well-being (Ardestani et al, 2022;Makhasane & Majong, 2023).…”
Section: Background and Problem Statementmentioning
confidence: 99%
“…An increasing number of scholars have shifted research on SVB from what and why questions to a combined focus that also examines how to bring about change as well as the nature of such change (Ardestani et al, 2022;McMahon et al, 2022;Moreroa, 2022;Ngidi, 2018;Taole, 2016). Linked to SDG 3 (good health and well-being) and SDG4 (quality education for all), the radar is on how to promote schools that integrate value-driven education within the teaching-learning of subject specific content (Sayed, Salmon & Balie, 2020).…”
Section: Change Discoursementioning
confidence: 99%